Physiological and Differential Proteomic Analysis at Seedling Stage by Induction of Heavy-Ion Beam Radiation in Wheat Seeds - Li, Yuqi; Gu, Jiayu; Irshad, Ahsan; Zhao, Linshu; Guo, Huijun; Xiong, Hongchun; Xie, Yongdun; Zhao, Shirong; Ding, Yuping; Zhou, Libin; Kong, Fuquan; Fang, Zhengwu; et al. (Frontiers in Genetics, 2022)
Novel genetic variations can be obtained by inducing mutations in the plant which help to achieve novel traits. The useful mutant can be obtained through radiation mutation in a short period which can be used as a new material to produce new varieties with high yield and good quality wheat. In the present study, the wheat seedling was treated with different doses of 12C and 7Li ion beam irradiation and this was analyzed by a TMT labeling quantitative proteomic analysis platform based on high-resolution liquid chromatography-mass spectrometry and using conventional 60Co-γradiation treatment as a reference. A total of 4764 up-regulated and 5542 down-regulated differentially expressed proteins were identified. These proteins were mainly enriched in the KEGG pathway associated with amino acid metabolism, fatty acid metabolism, carbon metabolism, photosynthesis, signal transduction, protein synthesis, and DNA replication. Functional analysis of the differentially expressed proteins showed that the oxidative defense system in the plant defense system was fully involved in the defense response after 12C ion beam and 7Li ion beam radiation treatments. Photosynthesis and photorespiration were inhibited after 12C ion beam and 60Co-γ-ray irradiation treatments, while there was no effect on the plant with 7Li ion beam treatment. In addition, the synthesis of biomolecules such as proteins, as well as multiple signal transduction pathways also respond to radiations. Some differential proteins were verified by PRM and qPCR, and the experimental results were consistent with the quantitative results of TMT. The present study shows that the physiological effect of 12C ion beam radiation treatment is different as compared to the 7Li ion beam, but its similar to the 60Co-γ ray depicting a significant effect on the plant by using the same dose. The results of this study will provide a theoretical basis for the application of 12C and 7Li ion beam radiation in the mutation breeding of wheat and other major crops and promote the development of heavy ion beam radiation mutation breeding technology.